Aberrant FGFR signaling mediates resistance to CDK4/6 inhibitors in ER+ breast cancer - Luigi Formisano (Nature Portfolio, 2019)
Era+ breast cancer patients often develop resistance to endocrine therapy. Here, the authors show that FGFR1 amplification is a resistance mechanism to CDK4/6 inhibitor and endocrine therapy and that combined treatment with FGFR, CDK4/6, and anti-estrogens is a potential therapeutic strategy in Era+ breast cancer tumors.